THE INFLUENCE OF WORK STRESS ON TURNOVER INTENTION: EMPLOYEE PERFORMANCE AS MEDIATOR IN CASUAL-DINING RESTAURANT - Suswati, Endang (Jurnal Aplikasi Manajemen, 2020)
The purpose of this study was to examine the effect of work stress on employee performance, the effect of employee performance on turnover intentions, work stress on turnover intentions, and examine the indirect effect of work stress on turnover intentions through employee performance as mediation. This research was conducted on employees of casual-dining restaurants in the city of Malang, East Java. The analysis model uses Partial Least Square. The results showed that work stress has a significant negative effect on employee performance, employee performance has a significant negative effect on turnover intention, work stress has no significant effect on turnover intention. The indirect effect of proven work stress has a significant effect on turnover intention through employee performance as mediation. For the development of science, the results of this study can be the next research reference material related to work stress, employee performance, and turnover intention.